Rendimiento en el aserrado por grados de calidad para remanufactura en taxones de pinos en el NE de Argentina - Winck, Rosa Ángela; Belaber, Ector; Bulman Hartkopf, Christian; Aquino, Diego Rolando; Rotundo, Cristian Andres; Gauchat, Maria Elena; Fassola, Hugo Enrique (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2023)
The remanufacturing industry is a very attractive option to improve the competitiveness of sawmills. The objective of this work was to evaluate the sawn timber of 42 basal logs from trees of 7 different taxas, in Factory grades, in wich the presence of knots is the main characterist. The higher yield of lumber, in m3, for the remanufacturing industry, was obtained with F1, PT and PEE × F1 taxas, also for the dominant stratum. The genetic material F1 proved to be a possible alternative to produce a greater amount of wood with greater added value according to the Factory standard.